STUDI KOMPARASI PEMIKIRAN AL-GHAZALI DAN IBNU TAIMIYAH TENTANG MEKANISME PASAR - Bela Selvia Febriyanti; Muhtadi Ridwan; Khusnudin Khusnudin (UNIVERSITAS MUHAMMADIYAH METRO, 2025)
Markets have an important position in the economy. Islam acknowledges the existence of a market mechanism on condition that the market can function perfectly. However, in reality, there are often market distortions caused by the seller's mistake. So from that, this study aims to clarify how Al-Ghazali and Ibnu Taimiyah think about the market mechanisms and regulation of the market mekanisms that exist at the moment. The methodology used in this writing is a qualitative method of library study, i.e. studying ideas and findings contained in articles or, journals, books, dissertations related to scientific information. The results of this study suggest that Al-Ghazali and Ibnu Taimiyah agreed on price setting, that is, that prices are fixed through the power of supply and demand, only in cases where prices rise due to the occurrence of unfairness and inequality of market mechanisms, then the government can interfere in setting prices.